O cuidado e a prescrição farmacêutica - Forgerini, Marcela (Editora Oficina Universitária, 2023)
This book is a joint effort by professors, graduate students, scientific initiation and university extension students at the Faculty of Pharmaceutical Sciences at UNESP and collaborating friends from the Federal University of São Paulo (UNIFESP), University of São Paulo (USP-RP) , Federal University of Bahia (UFBA) and Faculdades Oswaldo Cruz (FOC). The work aims to support teaching, research and extension activities in Pharmaceutical Care, at undergraduate, graduate and stricto and lato sensu graduate levels and pharmaceutical professionals in their professional practice.